Hyperoxia Is Not Associated With 30-day Survival in Out-of-Hospital Cardiac Arrest Patients Who Undergo Extracorporeal Cardiopulmonary Resuscitation - Kobayashi, Mioko; Kashiura, Masahiro; Yasuda, Hideto; Sugiyama, Kazuhiro; Hamabe, Yuichi; Moriya, Takashi (Frontiers in Medicine, 2022)
Introduction The appropriate arterial partial pressure of oxygen (PaO2) in patients undergoing extracorporeal cardiopulmonary resuscitation (ECPR) for out-of-hospital cardiac arrest (OHCA) remains unclear. The present study aimed to investigate the relationship between hyperoxia and 30-day survival in patients who underwent ECPR. Materials and Methods This single-center retrospective cohort study was conducted between January 2010 and December 2018. OHCA patients who underwent ECPR were included in the study. Exclusion criteria were (1) age <18 years, (2) death within 24 h after admission, (3) return of spontaneous circulation at hospital arrival, and (4) hypoxia (PaO2 < 60 mmHg) 24 h after admission. Based on PaO2 at 24 h after admission, patients were classified into normoxia (60 mmHg ≤ PaO2 ≤ 100 mmHg), mild hyperoxia (100 mmHg < PaO2 ≤ 200 mmHg), and severe hyperoxia (PaO2 > 200 mmHg) groups. The primary outcome was 30-day survival after cardiac arrest, while the secondary outcome was 30-day favorable neurological outcome. Multivariate logistic regression analysis for 30-day survival or 30-day favorable neurological outcome was performed using multiple propensity scores as explanatory variables. To estimate the multiple propensity score, we fitted a multinomial logistic regression model using the patients' demographic, pre-hospital, and in-hospital characteristics. Results Of the patients who underwent ECPR in the study center, 110 were eligible for the study. The normoxia group included 29 cases, mild hyperoxia group included 46 cases, and severe hyperoxia group included 35 cases. Mild hyperoxia was not significantly associated with survival, compared with normoxia as the reference (adjusted odds ratio, 1.06; 95% confidence interval: 0.30–3.68; p = 0.93). Severe hyperoxia was also not significantly associated with survival compared to normoxia (adjusted odds ratio, 1.05; 95% confidence interval: 0.27–4.12; p = 0.94). Furthermore, no association was observed between oxygenation and 30-day favorable neurological outcomes. Conclusions There was no significant association between hyperoxia at 24 h after admission and 30-day survival in OHCA patients who underwent ECPR.